Urban growth studies for the Holy City of Makkah, Saudi Arabia, through literature synthesis - Yahya M., Nabhan; Hashim, Abdullahi; Abdullah S., Karban; Lamit, Hasanuddin; Azizui, Muhammad; Asmawi, M. Zainora (Hunan University, 2023)
Urban growth in the Holy City of Makkah witnessed many changes from the beginning of the city, led by religious, economic, and political factors. The study aims to evaluate the trend of urban growth in Makkah, Saudi Arabia; it employed a systematic literature approach categorized into three for evaluating previous studies in this study for urban growth and expansion studies in Makkah. The first category covers the body of literature on the Kingdom of Saudi Arabia with a connection to the Arab nations and receives 27% of the scholars’ contributions. The second category covers the literature related to the Kingdom of Saudi Arabia cities and depicts 41% of the scholars’ contributions. The third category demonstrates literature specially conducted on the Holy City of Makkah and depicts 32% of the scholars’ contributions. The study handles 20 years of urban growth in Makkah from 1998 to 2013 with four study periods 1998, 2003, 2008, and 2013. The study indicates that scholars are making great efforts to study urban growth in Makkah. This study strongly recommends further studies on Makkah's urban growth using GIS and remote sensing technologies that will provide the information needed for future rational decision-making on urban growth management in Makkah.